Changes in Discard Rate After the Introduction of the Kidney Donor Profile Index (KDPI). Issue 7 (22nd March 2016) - Bae, S.; Massie, A. B.; Luo, X.; Anjum, S.; Desai, N. M.; Segev, D. L.
Abstract: Since March 26, 2012, the Kidney Donor Profile Index (KDPI) has been provided with all deceased‐donor kidney offers, with the goal of improving the expanded criteria donor (ECD) indicator. Although an improved risk index may facilitate identification and transplantation of marginal yet viable kidneys, a granular percentile system may reduce provider–patient communication flexibility, paradoxically leading to more discards ("labeling effect"). We studied the discard rates of the kidneys recovered for transplantation between March 26, 2010 and March 25, 2012 ("ECD era, " N = 28 636) and March 26, 2012 and March 25, 2014 ("KDPI era, " N = 29 021) using Scientific Registry of Transplant Recipients (SRTR) data. There was no significant change in discard rate from ECD era (18.1%) to KDPI era (18.3%) among the entire population (adjusted odds ratio [aOR] =0.97 1.041.10, p = 0.3), or in any KDPI stratum. However, among kidneys in which ECD and KDPI indicators were discordant, "high risk" standard criteria donor (SCD) kidneys (with KDPI > 85) were at increased risk of discard in the KDPI era (aOR =1.07 1.421.89, p = 0.02). Yet, recipients of these kidneys were at much lower risk of death (adjusted Risk Ratio [aRR] =0.56 0.770.94 at 2 years posttransplant) compared to those remaining on dialysis waiting for low‐KDPI kidneys. Our findings suggest that there might be an unexpected, harmful labeling effect of reporting a high KDPI for SCD kidneys, without the expected advantage of providing a more granular risk index. Abstract : Providing the Kidney Donor Profile Index (KDPI) with deceased donor kidney offers is associated with increased discards of standard criteria donor kidneys with KDPI > 85, a subgroup where the old standard/extended criteria donor designation and the new KDPI scoring deliver opposing messages, suggesting the possibility of a labeling effect.